2006
DOI: 10.1029/2006ja011742
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric disturbances during the magnetic storm of 15 July 2000: Role of the fountain effect and plasma bubbles for the formation of large equatorial plasma density depletions

Abstract: [1] We investigate the role of the fountain effect and plasma bubbles for the formation of the large equatorial plasma depletions during the geomagnetic storm of 15 July 2000. The large equatorial plasma depletions are detected in the Atlantic sector on the night of the 15th by the Defense Meteorological Satellite Program (DMSP) F15 and the first Republic of China Satellite (ROCSAT-1). The observations show discontinuous drop of the plasma density at the walls of the depletions, flat plasma density inside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…It involves significant ionospheric height rises and electron-density depletions. Kil and Paxton (2006) have noted that plasma bubbles are always present at these times and so used the term storm-induced big bubbles ((SIBB). In summarizing SIBB results Kil et al (2006) state [1] "They occur in the equatorial region at night, are elongated in the north-south direction, have steep walls, and always coexist with plasma bubbles."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It involves significant ionospheric height rises and electron-density depletions. Kil and Paxton (2006) have noted that plasma bubbles are always present at these times and so used the term storm-induced big bubbles ((SIBB). In summarizing SIBB results Kil et al (2006) state [1] "They occur in the equatorial region at night, are elongated in the north-south direction, have steep walls, and always coexist with plasma bubbles."…”
Section: Discussionmentioning
confidence: 99%
“…Kil and Paxton (2006) have noted that plasma bubbles are always present at these times and so used the term storm-induced big bubbles ((SIBB). In summarizing SIBB results Kil et al (2006) state [1] "They occur in the equatorial region at night, are elongated in the north-south direction, have steep walls, and always coexist with plasma bubbles." Satellite recordings by Lee et al (2002) have detected displacements of over 1400 km along a satellite path and a disturbance which extends at least 4500 km in the longitudinal direction.…”
Section: Discussionmentioning
confidence: 99%
“…Mannucci et al [2005] reported the abnormal enhancement of the total electron content (TEC) in low latitudes during the storm of October [29][30][31]2003 and attributed this phenomenon to the large increase in the upward E Â B drift velocity. The enhancement of TEC and upward E Â B drift velocity were also observed during the storm of July 15, 2000 [e.g., Basu et al, 2001;Kil and Paxton, 2006]. While these observations support the presence of severe disturbance electric fields during very large storms, we do not know yet whether this phenomenon occurs repeatedly during large storms or can also occur during smaller storms.…”
Section: Introductionmentioning
confidence: 91%
“…The nominal data rate was 1 Hz, but the ion density could be given at a rate as high as 1024 Hz [ Le et al , 2003]. As the low inclination angle (35°) distinguishes it from other ionospheric missions, the data was included in a large number of studies as a part of a multi‐instrumental data set [ Le et al , 2003; Burke et al , 2004; Kil et al , 2004; Kil and Paxton , 2006; S. M. Park et al , 2008].…”
Section: Instrumentationmentioning
confidence: 99%